Bad Smells in Javascript - A Mapping Study - Barros, Aryclenio Xavier; Adachi, Eiji (Anais do Workshop de Visualização, Evolução e Manutenção de Software (VEM); 2021: Anais do IX Workshop de Visualização, Evolução e Manutenção de Software, 2021)
Javascript is one of the most famous mainstream programming languages nowadays. It has gained considerable practical relevance over the last years, with applications in several areas, such as games, 3D rendering, and, mainly, web development. Like any other software system, systems developed in Javascript need to keep their ability to evolve to remain useful and relevant over time. Empirical evidence has shown that bad smells are possible indicators of problems hindering software evolvability. In this context, this paper presents a mapping study investigating if and to what extent bad smells have been defined for the Javascript language and how the interest in this topic has evolved. Our study identified 26 different types of bad smells investigated in the context of Javascript in 8 different works published between 2013 and 2020. This result suggests that although Javascript has gained practical relevance in recent years, there is still room for further empirical studies defining and evaluating the impact of bad smells on Javascript-based software systems.